Unusual Volume Reduction of Galassi Grade III Arachnoid Cyst Following Head Trauma - Prokopienko, Marek; Kunert, Przemysław; Marchel, Andrzej (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2013)
We report the case of a 36-year-old woman with a Sylvian fissure arachnoid cyst, which diminished after head trauma and minor hemorrhage into the cyst. We discuss the relationship between the cyst volume reduction and the head trauma to determine the main mechanism of this self-healing process.
Keywords: arachnoid cyst; sylvian fissure; head trauma